Combined hysterolaparoscopy as an early option for initial evaluation of female infertility: a retrospective study of 135 patients - Begum, Jasmina; Samal, Sunita; Ghose, Seetesh; Palai, Pallavee; Samal, Rupal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of this study was to find out different causes of female infertility with diagnostic approach using laparoscopy and hysteroscopy. Methods: This retrospective study was done in the Department of Obstetrics and Gynecology of MGMCRI, Puducherry. 135 infertile women aged 19-40 years were enrolled retrospectively for combined laparoscopy and hysteroscopy. These infertile women were confirmed to have normal ovulatory cycles, hormonal assays and seminogram report. Patient with active genital tract infection and any contraindication to hysterolaparoscopy procedure were excluded. Dye studies as well as inspection for abnormal pelvic and intrauterine pathology and necessary therapeutic interventions were done during the procedure. Abnormal pelvic and intrauterine pathology by hysterolaparoscopy were categorized. Data was statistically analyzed using SPSS software version 15; a result of P <0.05 was considered as significant. Results: Out of 135 cases, 65% patients had primary and 34.8% patients had secondary infertility. As a whole pelvic pathology were confirmed in 54.5% and intrauterine pathology in 20.7% patients by hysterolaparoscopy. The most common laparoscopic abnormality detected was tubal pathology 40%, followed by pelvic inflammatory disease 18.5%, ovarian pathology 8.1% pelvic endometriosis 4.4%, and uterine pathology 4.4% in infertile patients. In hysteroscopy, the incidence of uterine anomaly was 9.6% and intrauterine septum is the most common anomaly with a mean incidence of approximately 84% in both the group of infertile patients. Conclusions: Hysterolaparoscopy is an effective diagnostic tool for evaluation of certain significant and correctable abnormalities in pelvis, tubes and the uterus which are usually missed by other imaging modalities.